COMMUNITY DIAGNOSTIC DALAM UPAYA PROMOTIF DAN PREVENTIF PENYAKIT HIPERTENSI DI RT 03 DRUWO, BANGUNHARJO, SEWON, BANTUL, DAERAH ISTIMEWA YOGYAKARTA - Tri Wahyuni Sukesi; Putri Anisa Widyastuti (Jurnal Kesehatan dan Pengelolaan Lingkungan, 2023)
Hypertension or high blood pressure if a person experiences an increase in systolic blood pressure of more than 140 mmHg and diastolic pressure of more than 90 mmHg on an ongoing basis. In this study, the method used is descriptive quantitative through Community Diagnostic USG (Urgency, Seriousness, Growth), which aims to determine the existence of a health problem by collecting data from the community. The location is at RT 03 Padukuhan Druwo, Bangunharjo, Sewon Bantul, DI Yogyakarta which will be held on April 12-July 08 2022 with a team consisting of 1 lecturer and 1 student. Based on Community Diagnostics, it was found that hypertension was the main problem at the service location. Another problem is the community's non-compliance with taking hypertension drugs regularly and the community will regularly check their blood pressure, either personally to health services or during community health services. To overcome these problems, intervention was carried out in the form of direct counseling and using posters. The results obtained are that there is an increase in the average knowledge about hypertension after counseling. This is indicated by the average value of knowledge before counseling is 70 and after counseling the average value increases to 90. Appropriate interventions can provide increased knowledge and in the end are expected to increase public knowledge in preventing hypertension.